Design and analysis of CMOS-based terahertz integrated circuits by causal fractional-order RLGC transmission line model - Shang, Yang (2013)
A causal and compact fractional-order model is developed for complementary metal–oxide–semiconductor (CMOS) on-chip transmission line (T-line) at Terahertz (THz) frequencies. With consideration of the loss from frequency-dependent dispersion and nonquasi-static effects at THz, good agreement of characteristic impedance is observed between the proposed fractionalordermodel and the measurement up to 110 GHz, while traditional integer-order model can only match up to 10 GHz. The developed fractional-order model is further deployed in the design and analysis of CMOS-based THz integrated circuits that utilize T-line, such as standing-wave oscillator, which has significantly improved accuracy with causality.